Schengen Borders as Lines that Continue to Separate? Media Representations of Pandemic Dimensions of Insecurity in Eastern German Border Regions to Poland. Issue 4 (8th August 2022) - Renner, Nona; Miggelbrink, Judith; Beurskens, Kristine; Zitterbart, Antonia
ABSTRACT: At the internal Schengen borders, integration has long been a guiding paradigm. Nevertheless, it has never been an uncontroversial value. During the COVID-19 pandemic, demands for border closures within the Schengen space were characterized by a new urgency driven by biopolitical attempts to safeguard the respective communities. Our article focuses on the East German border regions to Poland in this conflicting situation. In the light of this crisis, the publicly shared stories and pictures of people living alongside this border demonstrated the strong entanglement of everyday life at this border. By means of an analysis of media articles published during the first two waves of the lockdown, the paper carves out how dimensions of insecurities in the border region arise due to contested negotiations over national orientations and integration. When the borders were shut down in March 2020, media coverage showed strongly rising protest in German–Polish borderlands, from medical staff and care workers, from students and trade people, from artists as well as local administrations. The responses to the COVID-19 pandemic show the potential to fuel debates on resurging nation–state-based politics and to promote nationalist, populist and reactionary positions, seizing upon insecurities and campaigning with emotional politics.